Women's Social Construction In Tradition Hunting Pig At Tanah Datar District - Syukri, Alfi; Rustim (Psychosocia : Journal of Applied Psychology and Social Psychology, 2023)
This paper aims to discuss the involvement of women in the tradition of hunting pigs at Tanah Datar District. Pig hunting in West Sumatra is a hereditary tradition carried out by the Minangkabau people which aims to eradicate pig pests that damage people's crops and plantations. Pig hunting is generally carried out by adult men in Minangkabau, where hunting is also an identity for men. adults in Minangkabau. However, since the last 10 years Minangkabau women have started to get involved in pig hunting. This research is a case study of Minangkabau women involved in the present tradition of hunting pigs. The method used in this research is a qualitative method where this research intends to understand what phenomena are experienced by research subjects, for example behavior, perceptions, motivations, actions holistically. For this reason, steps and research techniques were carried out such as Observation Techniques, Interview Techniques and Data Analysis, and Literature Studies. The theories used are Social Construction theory, Gender theory. Gender theory identifies the involvement of women in hunting pigs at Tanah Datar District.